The cell autonomous and non-autonomous roles of itaconate in immune response - Chao Chen; Xinjian Li (Cell Insight)
Itaconate which is discovered as a mammalian metabolite possessing antimicrobial and immunoregulatory activity has attracted much attention in the field of immunometabolism. Itaconate is synthesized by myeloid cells under conditions of pathogen infection and sterile inflammation. In addition to regulating immune response of myeloid cells, itaconate secreted from myeloid cells can also be taken up by non-myeloid cells to exert immunoregulatory effects in a cell non-autonomous manner. In this review, we recap the discovery of itaconate as a distinct immunologic regulator and effector, describe the development of itaconate biosensor, and detail the recent findings that decipher the mechanism underlying intercellular transport of itaconate. Based on these knowledges, we propose itaconate is a messenger transmitting immunologic signals from myeloid cells to other types of cells during host inflammation and immune defense.